If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x = 6x + 6 Reorder the terms: 7x = 6 + 6x Solving 7x = 6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 7x + -6x = 6 + 6x + -6x Combine like terms: 7x + -6x = 1x 1x = 6 + 6x + -6x Combine like terms: 6x + -6x = 0 1x = 6 + 0 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| x+5y=33 | | 3x^2+3y^2=48 | | 6*-2/3+8 | | 4+2x=5x+16 | | x+3=25/5 | | n^2-19n+88= | | 3/3x2-5x-2 | | 9-9/10 | | 15y-9=36 | | 3y^2-5=16 | | 19.36+22.93= | | 3x^2=17-20 | | 10000=19.36+22.93 | | 10p-9-2p+12= | | 21-(5-21)*5/8 | | 12-24*(-5/8) | | -7x-7=63 | | 5a+10b=30 | | 0.5p^2=4p-8 | | -2a^2+6a=5 | | 9m-16=m | | 5*8+9+4=53 | | 0.5/2.5 | | 145000000/1.16= | | -x^2-15x+4=0 | | 5*(8+9)+4=89 | | 2x-25=55 | | 504*.14= | | 5b+2p=144 | | (15n^2-5n+45)/5 | | 6y+16=-4y-4 | | X^2=y^2+9 |